New Half-Metallic Materials: FeRuCrP and FeRhCrP Quaternary Heusler Compounds - Ma, Jiannan (Materials (Basel), 2017)
The electronic structures and magnetic properties of FeRuCrP and FeRhCrP quaternary Heusler compounds with LiMgPbSb-type structures have been investigated via first-principles calculations. The calculational results show that both FeRuCrP and FeRhCrP compounds present perfect half-metallic properties: Showing large half-metallic band gaps of 0.39 eV and 0.38 eV, respectively. The total magnetic moments of FeRuCrP and FeRhCrP are 3 μB and 4 μB per formula unit, respectively. The magnetism of them mainly comes from the 3d electrons of Cr atoms and follows the Slater-Paulig behavior of Heusler compounds: M(t) = Z(t) − 24. Furthermore, the half-metallic properties of FeRuCrP and FeRhCrP compounds can be kept in a quite large range of lattice constants (about 5.44–5.82 Å and 5.26–5.86 Å, respectively) and are quite robust against tetragonal deformation (c/a ratio in the range of 0.94–1.1 and 0.97–1.1, respectively). Moreover, the large negative cohesion energy and formation energy of FeRuCrP and FeRhCrP compounds indicate that they can be synthesized experimentally.